(3JGQjN eQGcTs - (3eMeO Hf eMeO Hf YHO Gddg, GHf GdehbJ GdeQGcTj,J (B1369 (3g` s
(3ChdgG (B:s
(3HSYGOI GHOjI aGSJeSc (B/ (3hYdi efGgLgG GdaNjeI Yhd MeOkG def Rjf cd HdO HNGUI YHjQgG CeG HYO ajbhd Cf Chdi eG GfJgVJ Gdjg Gdgee GdJYQja ddeXGgQ GdeMeOjI s
(3BNQgG (B:s
(3dJROGO QZHI ef hba Ydjg ai JYXje gPG GdLfGH GdeLed ai GdMGd hGdGSJbHGd hai gPG GdbOQ caGjI s
(3GdfSNI HgG MhGTs
(3HChdg agQS eQbes
(3hgh LRFjfhHg fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3eJaQbGJs